Contingent Work and Organizational Attitudes in Family versus Non-Family Firms. An Analysis of the Hospitality Industry in Campania Region - Russo, Marcello (Piccola Impresa / Small Business, 2011)
The purpose of the research is to compare contingent workers’ organizational attitudes in family firms and nonfamily firms. In the current study, I propose and test a model in which contingent workers’ organizational identification, organizational commitment and job satisfaction are hypothesized to vary in family and nonfamily firms. The hypotheses were tested among high rank hotels in the Campania region. The empirical findings show that contingent workers in nonfamily hotels have higher levels of organizational commitment and job satisfaction than contingent workers in family hotels. Contingent workers show no differences with regard to organizational identification. Implication for theory and practice are discussed